Comprehensive evaluation of fertilizer treatments on biometric traits and marketable tuber weight across diverse potato varieties - Sibirev, Alexey (Frontiers in Sustainable Food Systems, 2024)
The process of establishing patterns between the amount of fertilizer application (“Aquarin 12”, “Bona Forte”, “Osmocote Exact High K”), their type and biometric characteristics of potato plants of the studied varieties “Guliver”, “Beauty of Meshchera” and “Grand” was explored. During the experimental studies, the methods of variation statistics, the technique of field experiment with the corresponding transformations to achieve normal distribution, and subsequent dispersion analysis were used. The results of the research on the evaluation of potato structural elements depending on the plant nutrition system of the studied varieties testify to the expediency of using nutrient solutions in potato cultivation irrespective of their type. In addition, it has been established that increasing the concentration of the nutrient base solution from 75% to 125% of the nutrient formula improves the quality indicators of minitubers, namely the content of starch, sugars, dry matter, crude protein, phosphorus, specific gravity and ash content, which can contribute to obtaining high-quality potatoes. Thus, the use of morphological and physiological tools in closed ecosystems is informative for predicting key agricultural characteristics of potato plants.